MODEL KEBIJAKAN PEMERINTAH DALAM PENGEMBANGAN PARIWISATA DI KOTA SAMARINDA - Prakoso, Cathas Teguh (Magister Ilmu Administrasi Negara Universitas Mulawarman, 2018)
This article aims to describe and analyse the policy model made by government to develop tourism sector in Samarinda. The policy is based on the assumption that the tourism policy of Samarinda has not delivered its potential to increase tourism sector. This research is decriptive with qualitative methode. Primary data are collected through interviews with both government and non-government informants. Secondary data are collected by screening related regulations and documents and then analysed by interactive methode. The research finds that Samarinda tend to develop a metropolitan based tourism rather than traditional one, while the policy itself is formulated using rational model.With Keywords: tourism development, public policy model, Samarinda